Educational management and school management: Training process of managers and the implications on educational practice (Revista Contexto & Educação, 2026)
The theme of this article is educational management and school management, in the process of training managers, with implications for educational practice. A reflection is proposed on the relevance and clarity of the expressions educational management and school management; presenting a more integrated education in a humanized way based on the training of managers and competent educational practice, based on the positioning of different authors. The research had a bibliographic and documentary nature, which contributed to guiding and developing the ideas of the work. The results allow us to verify the importance of education that contributes more intensely to the effective training of managers in both the scientific and human fields. There is a perceived need to understand the relevance of training managers, with implications that affect educational practice and require actions and interventions in favor of broader training from the perspective of human beings, arising from the involvement and training of managers/leaders combined with effectiveness and efficiency in line with the educational task and its interferences.
Keywords: Education; Educational management; School management; Training of managers